2016
DOI: 10.1039/c5an02121a
|View full text |Cite
|
Sign up to set email alerts
|

Robust NMR water signal suppression for demanding analytical applications

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This issue has also been mentioned in at least one other paper. 44 However, a recent study 48 showed that pulse sequences sensitive to gradient imperfections could still give good line shape by alternating gradient signs between scans. In that case, the WATERGATE water suppression scheme was used, but as we show here the scheme seems to be useful for other pulse sequences, including PURGE.…”
Section: Alternate Water Suppression Techniques and Avoiding Some Of mentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has also been mentioned in at least one other paper. 44 However, a recent study 48 showed that pulse sequences sensitive to gradient imperfections could still give good line shape by alternating gradient signs between scans. In that case, the WATERGATE water suppression scheme was used, but as we show here the scheme seems to be useful for other pulse sequences, including PURGE.…”
Section: Alternate Water Suppression Techniques and Avoiding Some Of mentioning
confidence: 99%
“…Our results confirm the utility of the PURGE pulse sequence, especially with the rather simple solution to compensate for gradient imperfections. 48 It should be noted that it is possible to adjust the pre-emphasis on most gradients. However, this is time-consuming and also specific for each probe.…”
Section: Alternate Water Suppression Techniques and Avoiding Some Of mentioning
confidence: 99%
“…Therefore, it was necessary to suppress the water signal very efficiently to allow for unambiguous identification of the methanol produced. This was achieved with the recently reported Robust-5 pulse sequence 23 (see experimental section for details). The results, presented in Figure 2, compare three sets of measurements: (i) ultrapure water placed for 5 seconds in contact with the surface of HOPG, (ii) ultrapure water placed for 2 hours in contact with the surface of HOPG, and (iii) ultrapure water placed for 2 hours in contact with the surface of HOPG while applying a DC potential of +1 V to the HOPG surface with respect to a platinum electrode placed directly in the water.…”
Section: Resultsmentioning
confidence: 99%
“…EDTA was tested in parallel to facilitate comparisons. To ensure the accuracy of stock ligand concentrations, we employed quantitative 1 H NMR spectroscopy with the ROBUST5 pulse sequence for solvent suppression, in the presence of an internal standard (t‐butanol), to determine the precise concentrations of the EDTA , AmGly 2 and AmPy 2 stock solutions. Such an approach is preferable to relying on inferred stock concentrations from the mass of ligand dissolved in a given volume of water, owing to the hygroscopicity of the ligands.…”
Section: Resultsmentioning
confidence: 99%